Structural Elucidation of Secondary Metabolites in Sponge (Callyspongia pseudoreticulata) with N-Hexane Extract - M. Nurdin; Hanapi Usman; Ambo Ala; Baharuddin Baharuddin (Hasanuddin University, 2014)
Sponge is one of the marine species that has a high bioactivity and contains secondary metabobolite compound which can be used as antibiotic and medicine. Terpenoid compound derivatives have been successfully isolated from sponge Callyspongia pseudoretilulata by a method in which the n-hexane extract weighing 11.28 g was fractionated using vacuum column chromatography with a non-polar eluent, n-hexane. The polarity of this eluent was improved by ethyl acetic resulting in fairly polar eluent, methanol. A total of 27 fractions were obtained and one of the compounds from n-hexane extract was structurally elucidated by NMR spectroscopy and two dimensions of homonuclear and heteronuclear (1H, 13C, DEPT, H-H COSY, HMQC, and HMBC). The identified compound was a hydrocarbon (1-ethyl cyclo hex cosana-1-amin) that indicated LC50 of 60.58 against A. salina and has a great potential as antitumor or anticancer.